1985
DOI: 10.1159/000145934
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulated Increases in Body Weight from Birth on the Growth of Limb Bones in Rats

Abstract: The purpose of this study was to subject groups of newborn male and female Sprague-Dawley rats each to a specific 10% simulated increase in body weight, to a maximum of a doubling of body weight, to study the effects of quantified, increased, intermittent, compressive forces on limb bone growth. Chronic centrifugation was employed. After 90 days of centrifugation the rats were sacrificed. The humerus, radius, ulna, femur, and tibia were removed from each animal, cleared of all soft tissues, measured and weighe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…When these results are compared with our findings in recent studies on the effects of simulated increases in body weight on the length of limb bones [Simon et al, 1984[Simon et al, . 1985b, definite parallels are revealed.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…When these results are compared with our findings in recent studies on the effects of simulated increases in body weight on the length of limb bones [Simon et al, 1984[Simon et al, . 1985b, definite parallels are revealed.…”
Section: Discussionmentioning
confidence: 54%
“…The results from the second of our two aforemen tioned studies [Simon et al, 1985b] have demonstrated that if rats are subjected to low levels of simulated in creases in body weight from birth, the adolescent growth period is not disturbed detrimentally. In fact, the data suggested that low levels of simulated increases in body weight (especially at 1.1 and 1.2 g) from birth enhanced the growth of limb bones; the controls had the shortest limb bones of any group.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In our earlier study investigating the effects of simulated increases in body weight from birth on limb bone length, the results revealed that both general body growth and limb bone length were enhanced (Simon et al, 1984~). The pattern suggested by the results of these two studies is one in which both limb bone length and bone robusticity are positively related with simulated increases in body weight, within the range used for these two studies.…”
Section: Discussionmentioning
confidence: 57%
“…During the last two decades, numerous studies were carried out to investigate the effect of hypergravitation on living organisms as a direct contrast to hypogravitation (i.e., zero gravity) loading which occurs in space [1][2][3][4][5][6][7][8]. Most of these studies have dealt with the effect of hypergravitation on bones, body mass and body composition.…”
Section: Introductionmentioning
confidence: 99%